Analysis of Offshore Wind Power Potential Considering Different Mesh Shapes in the Presence of Prevailing Wind and Deeper Water Depth: A Case Study in Akita, Japan - Takaaki Furubayashi; Komei Tsujie (Energies)
With countries around the world required to change their energy systems to mitigate climate change, offshore wind power has become one of the most important renewable energy sources. This study aims to analyze the potential for offshore wind power generation based on the water depth and annual average wind speed in the Akita region, Japan. A geographical information system was used not only for a conventional square mesh but also for a rectangular mesh when there is a prevailing wind, and a greater water depth was also considered. The results obtained indicate that the use of a rectangular mesh reduces the potential for implantable offshore wind turbines compared to a square mesh. It was also found that the potential for offshore wind power generation is significant up to a water depth of 500 m.